2004
DOI: 10.1128/aem.70.6.3535-3540.2004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the stx 2 Gene in Coliform Populations from Aquatic Environments

Abstract: Shiga toxin-producing Escherichia coli strains are human pathogens linked to hemorrhagic colitis and hemolytic uremic syndrome. The major virulence factors of these strains are Shiga toxins Stx1 and Stx2. The majority of the genes coding for these toxins are borne by bacteriophages. Free Stx2-encoding bacteriophages have been found in aquatic environments, but there is limited information about the lysogenic strains and bacteria present in the environment that are susceptible to phage infection. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 47 publications
3
48
0
Order By: Relevance
“…Although information is available about the occurrence of other virulence factors, such as STEC and Stx phages, in nonclinical settings (13,14,18), the same kind of study has not been reported for cdt. The present study was conducted (i) to determine the prevalence of cdt in STEC strains of nonclinical origin, (ii) to compare this incidence with non-STEC strains of nonclinical origin, and (iii) to elucidate whether bacteriophages, as free phages or associated with E. coli, could act as a reservoir and vehicle of transmission of cdt genes.…”
mentioning
confidence: 99%
“…Although information is available about the occurrence of other virulence factors, such as STEC and Stx phages, in nonclinical settings (13,14,18), the same kind of study has not been reported for cdt. The present study was conducted (i) to determine the prevalence of cdt in STEC strains of nonclinical origin, (ii) to compare this incidence with non-STEC strains of nonclinical origin, and (iii) to elucidate whether bacteriophages, as free phages or associated with E. coli, could act as a reservoir and vehicle of transmission of cdt genes.…”
mentioning
confidence: 99%
“…EAEC are defined as strains that do not secrete elt or sta gene products and that adhere to HEp-2 cells in an aggregativeadherence (AA) pattern [8]. EHEC, also known as Shiga toxinproducing E. coli or verocytotoxigenic E. coli [9], produces Shiga toxins (Stx1, Stx2, and their variants) as its major virulence characteristic, and the genes responsible for that are mostly bacteriophage borne [14,15]. EIEC elaborates the invasion plasmid antigen (ipaH), which is similar to Shigella species by means of genetic traits of virulence [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Contamination of the environment, followed by uptake of STEC by farm animals on pasture, maintains the epidemiological cycle of STEC and is a public health concern. In addition, data on the presence and characteristics of STEC in urban and slaughterhouse wastewater are limited and difficult to compare (11,12,14,18,22,37).…”
mentioning
confidence: 99%